Artificial Intelligence and Novel Services: Exploring Opportunities in the Marketing Landscape - Achmad Yanu Alif Fianto; Angga Dutahatmaja (Universitas Dinamika, 2023)
Customer loyalty and trust are critical factors for businesses aiming to establish long-term relationships with their customers. With the advancement of artificial intelligence (AI) technologies, there is a growing interest in leveraging AI to measure and enhance customer loyalty and trust. This research aims to explore the role of AI in measuring and enhancing customer loyalty and trust by examining the current literature and conducting empirical studies. The research methodology involves a systematic review of relevant studies and the development of a conceptual framework. The research results highlight the significant impact of AI on customer loyalty and trust, demonstrating how AI-powered solutions can effectively collect and analyze customer data to gain insights and personalize customer experiences. The discussion encompasses the implications of AI in measuring and enhancing customer loyalty and trust, including the importance of data privacy and ethics. The study concludes with recommendations for businesses on implementing AI strategies to build and maintain strong customer relationships based on loyalty and trust. Overall, this research contributes to the understanding of how AI can revolutionize customer relationship management and provides valuable insights for practitioners and researchers in the field of marketing and AI.